Short-term outcomes of neoadjuvant chemotherapy in colorectal cancer patients with isolated liver metastasis - A. Yu. Dobrodeev; D. N. Kostromitsky; A. S. Tarasova; S. G. Afanasyev; N. N. Babyshkina; A. A. Ponomaryeva; R. V. Ermolenko; I. G. Frolova; O. V. Cheremisina (Сибирский онкологический журнал)
The purpose of the study was to assess the short-term effcacy and tolerability of neoadjuvant chemotherapy (NAC) in colorectal cancer (CRC) patients with isolated liver metastasis.Material and Methods. Since 2020, a pilot study including 23 CRC patients with liver metastasis has been conducted at the Abdominal Cancer Department of the Cancer Research Institute (Tomsk, Russia). The combined treatment modality included 3 cycles of NAC according to FOLFOXIRI + cetuximab (20 patients with wtKRAS) and FOLFOXIRI + bevacizumab (3 patients with mtKRAS) regimens followed by simultaneous laparoscopic colorectal resection and open liver resection.Results. For liver metastases, the objective response rate reached 100 % (complete response: 8.7 %, partial response: 91.3 %). For the primary tumor, the objective response rate was 100 % (partial response). The overall NAC toxicity rate was 53.6 %. The major I–II grade toxicities included nausea/vomiting (27.5 %), polyneuropathy (10.1 %), skin reaction (10.1 %), hepatotoxicity (5.8 %), and corresponded to I–II grade. R0 resection was performed in all patients. Postoperative complications were observed in 19 (82.6 %) patients; of them 18 (78.3 %) had a febrile temperature (grade 1, according to the Clavien–Dindo classifcation) due to the use of bipolar coagulation during liver surgery, and 1 (4.4 %) patient developed a biliary fstula (3 A/B grade according to Clavien–Dindo). No postoperative death occurred. For liver metastasis, pathological complete response rate was 4.4 % (TRG1 according to Mandard); for the primary tumor, in most cases was TRG 3 – 87 %.Conclusion. Combined treatment modality, including NAC with FOLFOXIRI regimen and targeted therapy for CRC with liver metastases, is well tolerated, has a signifcant damaging effect on the tumor, and does not affect the course of the postoperative period. Further studies are required to assess the long-term treatment outcomes.